Antibacterial Activity of Ethanol Extract of Srikaya Leaves (Annona squamosa Linn) Against the Growth of Acne Vulgaris-Causing Bacteria Staphylococcus epidermidis - Amalia, Annora Rizky; Zulaika Febru Zalsabila; Yunita Dian Permata Sari (Scientific Journal of Dermatology and Venereology, 2025)
Introduction: Acne vulgaris, a prevalent skin condition, is primarily triggered by the proliferation of Cutibacterium acnes within pilosebaceous units. However, Staphylococcus epidermidis, a commensal skin bacterium, can exacerbate acne inflammation upon follicular invasion. This study investigates the antibacterial potential of ethanol extract derived from srikaya leaves (Annona squamosa Linn) against S. epidermidis. Methods: Srikaya leaves underwent ethanol extraction via maceration. The extract's antibacterial efficacy was assessed using the agar well diffusion method against S. epidermidis at varying concentrations (25%, 50%, 75%). Zones of inhibition were measured, and minimum inhibitory concentrations (MICs) were determined. Phytochemical screening of the extract was conducted to identify potential bioactive compounds. Results: The ethanol extract of srikaya leaves exhibited significant antibacterial activity against S. epidermidis. Increasing extract concentrations led to larger zones of inhibition, indicating a dose-dependent effect. The MIC of the extract against S. epidermidis was determined to be 50%. Phytochemical analysis revealed the presence of flavonoids, phenols, and alkaloids, which are known for their antimicrobial properties. Conclusion: Ethanol extract of srikaya leaves demonstrates promising antibacterial activity against S. epidermidis, suggesting its potential as a natural therapeutic agent for managing acne vulgaris. Further research is warranted to elucidate the mechanisms of action and evaluate the extract's efficacy in clinical settings.